PERTIMBANGAN HAKIM PENGADILAN TINGGI DALAM MEMERIKSA JUDEX FACTIE TERHADAP PENYALAHGUNA TINDAK PIDANA NARKOTIKA (STUDI KASUS PUTUSAN NOMOR 503/PID.SUS/PT PBR) - Hervi Alfathira Natasya; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Indonesia has long taken legal steps to tackle the dangers of narcotics, boththrough making regulations in the form of legislation by issuing Law Number 22of 1997 which is now Law Number 35 of 2009. In the case of decision Number503/ Pid.Sus/2022/PT Pbr case of narcotics use which in the verdict was chargedunder Article 112 Paragraph (1) of Republic of Indonesia Law Number 35 of2009 which ignored the facts of the trial (judex factie). The first aim of thisresearch is to analyze the High Court judges' considerations in examining thejudex factie case in decision number 503/Pid.Sus/2022/PT Pbr and find out thelegal consequences. The second is to find out about high court judges in handingdown judex factie decisions at the High/Appeal Court level.The type of research used in this research is normative juridical legalresearch or can also be called doctrinal legal research. Normative juridical legalresearch is library legal research. The research uses qualitative analysis whichproduces descriptive data.The results of this research examine the analysis that the verdict in casenumber 503/Pid.Sus/2022/PT Pbr, the defendant was sentenced to prison for 2(two) years 6 (six) months, this is below the minimum provisions that have beenregulated and give rise to The legal consequences should be Article 127Paragraph 1 letter a of the Narcotics Law which is applied in decision number503/Pid.sus/2022/PT Pbr and the defendant can be sentenced to criminalprovisions in accordance with the Law, namely a rehabilitation sentence. Article183 of the Criminal Procedure Code states that "a judge may not impose a crimeon a person unless, with at least two valid pieces of evidence, he is convinced thata criminal act has actually occurred and that the defendant is guilty." The judgecan make a decision according to the evidence and facts revealed at the trial.Keyword: Judex factie, Narcotic Crime, Judge.